2021
DOI: 10.3389/fenvs.2021.593220
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Changes of Near-Surface Ozone Concentration From 2015 to 2018 in Beijing

Abstract: In this study, we investigated the spatiotemporal changes of near-surface O3 concentration based on 33 automatic air quality monitoring stations in Beijing in 2015 and 2018. Here we show that the diurnal variations for O3 concentration at 33 monitoring stations exhibited a single-peak mode with a minimum concentration from 06:00 to 07:00 and a maximum value from 14:00 to 15:00. We find that the O3 concentration was significantly positively correlated with the air temperature, solar total radiation, and wind sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…Some studies have also reported negative correlation between high temperature and pollutants, stating that high temperature promotes convection of air, and brings about the dilution and dispersion of air pollutants ( Yang et al., 2017 ). Further, O 3 is very weakly correlated with temperature in post-lockdown phase, with the correlation not even significant, which is inconsistent with earlier studies ( Ali et al., 2012 ; Jayaraman et al., 2007 ; Xie et al., 2021 ).…”
Section: Resultscontrasting
confidence: 91%
“…Some studies have also reported negative correlation between high temperature and pollutants, stating that high temperature promotes convection of air, and brings about the dilution and dispersion of air pollutants ( Yang et al., 2017 ). Further, O 3 is very weakly correlated with temperature in post-lockdown phase, with the correlation not even significant, which is inconsistent with earlier studies ( Ali et al., 2012 ; Jayaraman et al., 2007 ; Xie et al., 2021 ).…”
Section: Resultscontrasting
confidence: 91%
“…The irradiation intensity was assumed to be 10 W m À 2 (peak average day value in Beijing in winter 2015). [22] (b) The increasing ratio of N 2 O 5 concentration after considering the new source generated from TiO 2 surfaces (10 % of urban surfaces is assumed to be covered by TiO 2 materials).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7. (a) N 2 O 5 formation rates (represented by the gradation of blue in the vertical bar) under different NO 2 concentrations (0-100 ppb) and different TiO 2 fractions on urban surfaces (0-30 %) at 20 % RH.The irradiation intensity was assumed to be 10 W m À 2 (peak average day value in Beijing in winter 2015) [22]. (b) The increasing ratio of N 2 O 5 concentration after considering the new source generated from TiO 2 surfaces (10 % of urban surfaces is assumed to be covered by TiO 2 materials).…”
mentioning
confidence: 99%